2021
DOI: 10.1210/jendso/bvab048.898
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Maternal Benzene Exposure Predisposes to the Metabolic Imbalance in the Offspring

Abstract: Environmental chemicals play a significant role in the development of metabolic disorders, especially when exposure occurs early in life. We have recently demonstrated that benzene exposure, at concentrations relevant to a cigarette smoke, induces a severe metabolic imbalance in a sex-specific manner affecting male but not female mice. However, the roles of benzene in the development of aberrant metabolic outcomes following gestational exposure, remain largely unexplored. In this study, we exposed pregnant C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…3C). Thus, prenatal benzene exposure alters hypothalamic leptin signaling of male offspring, affecting the organization of neural circuits that regulate energy homeostasis and glucose metabolism, which may contribute to sex-specific metabolic alterations previously observed in this model (8).…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…3C). Thus, prenatal benzene exposure alters hypothalamic leptin signaling of male offspring, affecting the organization of neural circuits that regulate energy homeostasis and glucose metabolism, which may contribute to sex-specific metabolic alterations previously observed in this model (8).…”
Section: Resultsmentioning
confidence: 81%
“…Indeed, increased offspring risk for cardiovascular and metabolic disease later in life has also been described in the context of the altered maternal environment, such as GDM, obesity, and exposure to environmental toxic compounds during pregnancy (57). In support, we have recently shown that gestational exposure to benzene at the levels relevant to cigarette smoking, induces deleterious effects on energy homeostasis, hyperglycemia, and insulin resistance in adult offspring (8). However, the mechanisms underlying fetal metabolic programming and predisposition to metabolic imbalance following gestational exposure to benzene remain unknown.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations